Language, ontology, and political philosophy in China : Wang Bi's scholarly exploration of the dark (Xuanxue). - WAGNER, RUDOLF G. (ALBANY : STATE UNIV OF NEW YORK PR, 2003)
"With the collapse of the Han dynasty in 220 C.E., an entire system of state and intellectual organization fell apart. The brilliant Wang Bi and his generation of young scholars grew up in a no-man's land without teachers and orthodoxy. Defying the established school divisions, they set out on a vigorous and daring new philosophical inquiry which came to be known as Xuanxue, the "Scholarly Exploration of the Dark." They found "subtle pointers" in the Laozi, the Book of Changes, and the Analects of Confucius about the inequity of language and the ensuing need to proceed by "subtle" indications that ultimately led to a philosophy of Being." "In this book, Rudolf G. Wagner shows how Wang Bi's sophisticated analysis of "subtle pointers" in the language of the Laozi developed into an ontology that served as the basis for a political philosophy of the ruler/subject relationship and a guide for the public performance of an enlightened ruler. Wang Bi's work initiated the reading of the Laozi, the Book of Changes and the Analects as philosophical texts and has had a lasting impact on Chinese philosophy."--Jacket.
Discerning the That-by-Which: The Language of the Laozi and the Lunyu -- A Plea for a History of Understanding -- The Consensus: The Ineffability of the Sage's Thinking -- The Radical Position -- Developing Reading Strategies -- The Discussion about Language and the Thinking of the Sage in Wei -- The Structural Contradiction of the Confucius Texts: Talking about That-Which-Is-Dark -- The Logical Deduction of the Unnameability of That-by-Which the Ten Thousand Kinds of Entities Are -- The Deduction of the Possibility of Limited but Sufficiently Grounded Propositions about That-by-Which the Ten Thousand Kinds of Entities Are -- Traces of the That-by-Which Found by the Confucius Texts within the Structures of Discernible Entities: Antinomy and Negation -- Grasping Aspects of the That-by-Which -- An Explanation of the Images [Xiang of the Zhouyi] -- Wang Bi's Ontology -- The Framework of Analysis -- Wang Bi's Inquiry into the That-by-Which -- Wang Bi's Approach -- The Binary Structural Organization of Entities -- The Order of the Ten Thousand Kinds of Entities -- The One and the Many -- The Dao -- The Dark -- Wang Bi's Political Philosophy -- The Actual and Perpetual Crisis of Human Society -- The Causes of the Crisis -- Operating the Return: The Sage -- Sagely Politics as Public Performance -- Wang Bi's Philosophy: An Ideology?
JSTOR
Keywords: Wang, Bi, -- 226-249.; Wang, Bi, -- 226-249; Wang, Bi -- 226-249; Wang, Bi; Philosophy, Chinese -- 221 B.C.-960 A.D.; Metaphysics; Metaphysics; Philosophie chinoise -- 221 av. J.-C.-960.; Métaphysique.; metaphysics; Taoist); RELIGION; Metaphysics; Philosophy, Chinese; Philosophie; China; Sprachphilosophie; Chinese filosofie; 221 B.C.-960 A.D.